Prognostic value of P-selectin and sST2 in patients with multiple myeloma - M. O. Panasenko; B. B. Samura; S. Ya. Dotsenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
Cardiac involvement is one of the most important prognostic markers in multiple myeloma. However, prognostic value of novel biomarkers, such as soluble suppression of tumorigenicity 2 (sST2), P-selectin is unknown in multiple myeloma.